The Impact of Nutritional Status and Body Mass Index on Rehabilitation Outcomes in Patients Receiving Home-Based Medical Care - Kanako Eiwa; Naomi Nakayama; Yumi Takami; Shuko Iwasaki; Yoshinori Hino; Takehiko Hirai; Kentaro Nakayama; Yuji Eda (World Nutrition Journal, 2020)
Background: Home-based medical care is expanding rapidly in Japan.Objectives: We aimed to identify the factors associated with outcomes of therapy in patients receiving home-visit rehabilitation.Methods: One hundred twenty-one patients receiving home-based rehabilitation were investigated. Nutritional status was assessed by the Mini Nutritional Assessment Short Form (MNA-SF). The Functional Independence Measure (FIM) was employed to assess the activities of daily living (ADL). The body mass index (BMI), medical history, and orthopedic disease-related pain were also recorded. The primary outcome was the improvement in FIM scores in one year.Results: A total of 19 (17%) patients were malnourished and 58 (48%) were at risk of malnutrition. Malnourished patients had a lower FIM score at initiation than those at risk of malnutrition or with normal nutritional status. Only changes in patients’ BMI and MNA-SF scores over one year were significantly associated with improved FIM scores (p = 0.0079 and p = 0.0049, respectively). No association was noted with the other factors.Conclusions: This is the first report to demonstrate that changes in MNA-SF scores and BMI are significantly associated with rehabilitation outcomes in home-based care. Nutritional management is essential along with rehabilitation to improve ADL in the long-term home care setting.